2021
DOI: 10.1101/2021.04.09.439171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rad53 checkpoint kinase regulation of DNA replication fork rate via Mrc1 phosphorylation

Abstract: The Rad53 DNA checkpoint protein kinase plays multiple roles in the budding yeast cell response to DNA replication stress. Key amongst these is its enigmatic role in safeguarding DNA replication forks. Using DNA replication reactions reconstituted with purified proteins, we show Rad53 phosphorylation of Sld3/7 or Dbf4-dependent kinase blocks replication initiation whilst phosphorylation of Mrc1 or Mcm10 slows elongation. Mrc1 phosphorylation is necessary and sufficient to slow replication forks in complete rea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…Moreover, during normal replication, Mec1 may locally activate Rad53 to deal with difficult to replicate regions or regions of replication-transcription conflict without triggering full blown checkpoint activation (Bastos de Oliveira et al, 2015). Rad53 kinase inhibits Mrc1 stimulation of the CMG helicase (McClure and Diffley, 2021), consistent with our observation that replication fork progression is limited in the absence of Mrc1 and that replication forks cannot be rescued after DNA damage in rad53 K227A cells (Forey et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, during normal replication, Mec1 may locally activate Rad53 to deal with difficult to replicate regions or regions of replication-transcription conflict without triggering full blown checkpoint activation (Bastos de Oliveira et al, 2015). Rad53 kinase inhibits Mrc1 stimulation of the CMG helicase (McClure and Diffley, 2021), consistent with our observation that replication fork progression is limited in the absence of Mrc1 and that replication forks cannot be rescued after DNA damage in rad53 K227A cells (Forey et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Following hydroxyurea induced replication stress, Rad53 was recruited to active origins of DNA replication and to DNA replication forks in a checkpoint independent manner since mrc1Δ and rad53 K227A mutants had little effect on binding. Rad53 is targeted to replisomes by the helicase subunits Cdc45 and Mcm2 where it is activated by Mec1 kinase dependent on Mrc1 at the fork, and stabilizes the replisome (Can et al, 2018; Cobb et al, 2005; Lou et al, 2008; McClure and Diffley, 2021; Szyjka et al, 2008). Maintenance of Rad53 at the replication forks requires Rad53 kinase activity but not DRC checkpoint signaling.…”
Section: Discussionmentioning
confidence: 99%
“…S1 H and I). Importantly, it has also been observed in other proteins that the phenotype of the phosphor-mimic mutation (serine or threonine to aspartate) is recaptured by the mutation of serine or threonine to alanine (80,81).…”
Section: Geneticsmentioning
confidence: 99%
“…[ 59,99 ] Other in vitro studies using a reconstituted replication system have elaborated that Mrc1 stimulates the activity of both the CMG helicase and Pol ε. [ 100,101 ] Further experiments using this system have shown that Rad53 phosphorylates Mrc1 and thereby suppresses its ability to stimulate DNA synthesis. Together, we propose that Rad53 phosphorylates Mrc1, which in turn slows down leading strand DNA synthesis under replication stress.…”
Section: Mechanistic Insights Into How Rad53 Couples Leading and Lagg...mentioning
confidence: 99%
“…Other studies have shown that Rad53 phosphorylates Mrc1, which may in turn inhibit the ability of Mrc1‐Tof1‐Csm3 to stimulate CMG helicase activity and potentially the activity of Pol ε as well. [ 8,88,100 ] Therefore, we hypothesize that Rad53 phosphorylates multiple replisome components to slow down DNA synthesis of leading and lagging strands simultaneously (Figure 2). Because the machinery involved in leading and lagging strand DNA synthesis function autonomously in vitro, we further suggest that these actions couple leading and lagging strand DNA synthesis and thereby prevent deleterious ssDNA template exposure under replication stress.…”
Section: Mechanistic Insights Into How Rad53 Couples Leading and Lagg...mentioning
confidence: 99%